Facile and Direct Hydroxylation of Benzene to Phenol over Graphene‐Based Catalysts: Integrated Utilization of Greenhouse Nitrous Oxide. Issue 4 (26th March 2018) - Zhu, Chang; Yun, Jiena; Wang, Qian; Hu, Qiaoli; Yang, Gang
Abstract: Graphene catalysis has recently emerged as a focus and herein a novel and highly efficient process is computationally designed using graphene‐based catalysts that integrates the utilization of greenhouse nitrous oxide (N2 O) as oxidant. The ground‐state pristine graphene is not catalytically active for benzene hydroxylation, and doping and photocatalysis through excitations are employed to improve the catalyst systems, while both strategies exhibit limited effects. A combination of Be‐doping and photocatalysis through excitations results in encouraging changes, where all energy barriers are moderate, so that the whole catalytic processes proceed facilely at mild conditions. Graphene materials, especially Be‐ and O‐doped ones, are good photocatalysts due to the low excitation energies. Mechanistic studies indicate that the active sites of the excited‐state graphene, whether pristine or doped, are oxygen anion radical (O − ) and distinct from the epoxide species for the ground state; in addition, Be‐doping pronouncedly reduces the excitation energies and enhances the interactions with the active‐site O species, which further show strong stabilization effects to transition states and reduce substantially the energy barriers. Abstract : Graphene‐based catalysts are computationally designed for direct benzene hydroxylation to produce phenol. A combination of Be‐doping and photocatalysis through excitations causes all energy barriers to be moderate so that the whole catalytic processes proceed facilely at mild conditions. The active sites of excited‐state graphene materials are determined to be oxygen anion radical, as in the case of Fe/ZSM‐5 zeolite.